Design optimization of intake manifold of dual fuel engine. (2021) - Adithya, K.; Ahmed, Fareed; Padmanathan, P.; Mohan, C.G.; Prakash, R.
Abstract: This research is aimed to analyse and optimize the inlet manifold of biogas diesel dual fuel engine to improve the mass flow rate of air and gas mixture and hence improving volumetric efficiency of the dual fuel engine. Runner length of the inlet manifold is calculated using Chrysler Ram Theory and Helmholtz Resonator Theory and new runner length is replaced in the existing inlet manifold and it is observed that new runner length gives a considerable increase in mass flow rate of air and hence improving the volumetric efficiency. The biogas was collected from biogas plant of Vellore Institute of Technology and the diesel engine was operated with diesel and bio gas with the help of a T-section joint which allowed the air and bio gas to enter the engine together and then we performed the experiment to calculate the mass flow rate of air and bio gas entering the engine. The experiment was done for the existing runner length of 1 m and the new runner length of 1.58 m, as calculated by Chrysler Ram Theory and improvements were observed in mass flow rates and volumetric efficiency. Emission testing was also done by using the AVL emission system, emission-parameters-like-carbon-monoxide-(CO), -nitric-oxide-(NOx )-and hydrocarbon-(BSHC)-emissions-are-measured.